2020
DOI: 10.14710/jkli.19.2.76-81
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Berpengaruh terhadap Praktik Masyarakat dalam Pengelolaan Sampah di Desa Ketenger, Kecamatan Baturaden, Kabupaten Banyumas

Abstract: Latar belakang: Sampah merupakan masalah yang sulit ditangani. Setiap tahun timbulan sampah semakin meningkat, sehingga diperlukan pengelolaan sampah untuk mengurangi masalah. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berpengaruh terhadap praktik masyarakat dalam pengelolaan sampah di Desa Ketenger, Kecamatan Baturaden, Kabupaten Banyumas.Metode: Jenis penelitian adalah analitik observasional dengan pendekatan crossectional, jumlah sampel 102 responden, pengambilan sampel dilakukan dengan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Community concern is a willingness to take action or practice reducing waste around it [12]. Facilities and infrastructure have an influence on waste management practices, therefore the better the waste management facilities and infrastructure, the better the management of the surrounding environment [13]. Concept of Waste Management and Improvement of Waste Services by the Government The following concept framework can be seen below.…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…Community concern is a willingness to take action or practice reducing waste around it [12]. Facilities and infrastructure have an influence on waste management practices, therefore the better the waste management facilities and infrastructure, the better the management of the surrounding environment [13]. Concept of Waste Management and Improvement of Waste Services by the Government The following concept framework can be seen below.…”
Section: Results Anddiscussionmentioning
confidence: 99%
“…SeIama ini pengeIoIaan sampah beIum sepenuhnya sesuai dengan metode dan teknik pengeIoIaan sampah yang berwawasan Iingkungan sehingga menimbuIkan dampak negatif bagi kesehatan masyarakat dan Iingkungan (Widiyanto, 2020). SeIain itu, sarana dan prasarana pengeIoIaan sampah di Kota Semarang tidak sebanding dengan voIume sampah yang dihasiIkan sehingga kinerja peIayanan pengeIoIaan sampah tidak optimaI (Setyono et al, 2018).…”
Section: Pendahuiuanunclassified
“…The role of the mother as a waste manager is very important, housewives often carry out the involvement of managing waste in the household. Women can carry out waste management activities to contribute social capital and human capabilities (Widiyanto et al, 2020). The results of Ahmadi M (2017) research conducted on housewives in Tehran found that only 26% of the subjects participated in reducing at home.…”
Section: Reducementioning
confidence: 99%